Bridging the Gap Between Education and Experience: A Comparative Analysis of IPB University Museum's Visitor Experience - Dean Apriana Ramadhan; Syafitri Hidayati; Auzi Asfarian; Firman Ardiansyah (Program Studi Ilmu Perpustakaan UIN Alauddin, 2023)
The IPB Museum, located on the Darmaga Campus of IPB University, serves as a platform to showcase its rich history, developments, and future aspirations. University museums are vital institutions, embracing innovation and fostering communities of knowledge. Previous research emphasizes the impact of visitor experience on satisfaction and loyalty, highlighting the advantages of interactive technologies in museums for improved engagement and education. Evaluating technology's impact is crucial, and this study utilizes The Museum Tourism Experience and Experiential Value questionnaire to provide a baseline measurement and benchmark for future interventions, enabling a comprehensive evaluation of technology's impact on visitor experiences and satisfaction. In this study, 103 undergraduate students from the User Experience Design Course were invited to visit the IPB Museum to assess their experience using The Museum Tourism Experience and Experiential Value (MTEEV) questionnaire, which evaluates five aspects of the visitor experience. The students completed the questionnaire both before and after their visit, aiming to measure the impact of the museum visit on their perception and evaluate the effectiveness of the IPB Museum. The museum received lower ratings in visual appeal, entertainment, escapism, willingness to pay more, and imaginary vividness compared to visitors' past experiences, indicating potential areas for improvement to enhance the overall visitor experience. Lastly, we present our participatory strategy using MBKM and the capstone program to improve the museum experience.